Linguo-cultural features of sky metaphorization and celestial light in russian poetic discourse (Eurasian Journal of Philology Science and Education, 2019)
The article is devoted to the linguistic and cultural peculiarities of the metaphorization of the sky andthe heavenly bodies in the discourse of Russian poetry. Based on the analysis of the associative-semanticand emotional-aesthetic components of metaphorization, its linguocultural features are determined. Thefigurative and symbolic meaning of the tokens «sky», «heaven», «moon», «sun», «clouds», «stars» is determined. Metaphorization of the sky and the heavenly bodies in poetic discourse testifies to the dualityof perception of the sky and the heavenly bodies by the Russian language consciousness. The sky andthe stars are associated not only with light, brilliance and beauty, but also with cold, emptiness, indifference and lifelessness. The linguo-cultural peculiarity of the metaphorization of the Moon is based ontraditional mythopoetic views. In the Russian language consciousness and in the poetic works of Russianpoets, Heaven and the Moon are contrasted on the basis of «male-female». The emotional metaphorization of the lexeme «Moon» is built on this conceptual antithesis: the moon is a separation, sadnessabout a dream, a night without the moon. The article notes that the metaphorization of the sky and theheavenly bodies in Russian poetry reflects not only the artistic individual author’s vision, but also thenational-cultural one.